Transorbital sonographic evaluation of normal optic nerve sheath diameter in healthy Nepalese adults - Shrestha, Gentle Sunder (Journal of Neuroanaesthesiology and Critical Care, 2016)
Background: Sonographic evaluation of optic nerve sheath diameter (ONSD) is increasingly being used as a non-invasive technique for detecting raised intracranial pressure. Aims: The aim of this study is to find out the normal ONSD in healthy Nepalese adults. Settings and Design: It is a cross-sectional observational study. Subjects and Methods: ONSD was measured 3 mm behind the globe using 6–13 MHz linear probe. Subjects were examined in the supine position with their eyes closed and in neutral position. Transducer was placed horizontally and in each eye, an average of three readings were documented. Statistical Analysis Used: Data were represented as mean and standard deviation. Paired t-test was used to compare ONSD between the right and left eye. Independent t-test was used to compare ONSD between males and females. Pearson correlation coefficient was used to assess the correlation between age and ONSD. Results: Eighty-eight healthy subjects above 18 years of age were enrolled in the study. The median ONSD was 4.1 mm with 95% of subjects in the range of 3.1–4.6 mm. There was no significant difference in ONSD measurement between males and females (P = 0.09) and between the right and left eye (P = 0.72). There was no relationship between ONSD and age ( R2=0.06, P = 0.55). Conclusions: The range for normal ONSD in healthy adult Nepalese subjects is 3.1–4.6 mm with no significant relationship with gender, age and side of the body.
Keywords: Nepalese adult; optic nerve sheath diameter; ultrasonography